Allahabadolactones A and B from the endophytic fungus, Aspergillus allahabadii BCC45335. Issue 4 (28th January 2016) - Sadorn, Karoon; Saepua, Siriporn; Boonyuen, Nattawut; Laksanacharoen, Pattiyaa; Rachtawee, Pranee; Prabpai, Samran; Kongsaeree, Palangpon; Pittayakhajonwut, Pattama
Abstract: Two new compounds, allahabadolactones A (1 ) and B (2 ), along with 10 known compounds including 16-amino-isopimar-7-en-19-oic acid (3 ), 16-α-d -glucopyranosyloxyisopimar-7-en-19-oic acid (4 ), 16-α-d -mannopyranosyloxyisopimar-7-en-19-oic acid (5 ), ergosterol, (22 E )-5α, 8α-epidioxyergosta-6, 22-dien-3β-ol, cerevisterol, ( R )-(−)-methoxycarbonylmellein, (−)-piliformic acid, 7-dechlorogriseofulvin, and cytochalasin D, were isolated from the endophytic fungus, Aspergillus allahabadii BCC45335. Their chemical structures were determined based on NMR spectroscopic and mass spectrometric analyses. The absolute stereochemistry of compound1 was established by an X-ray crystallographic analysis and the reactions with Mosher's reagents. A plausible biosynthesis of allahabadolactones A (1 ) and B (2 ) was also proposed. Antibacterial activity against Bacillus cereus and cytotoxicity against MCF-7, KB, NCI-H187, and Vero cells of the isolated compounds were also evaluated. Graphical abstract: